15(x+1)-5(10x+9)+2(5x+3)+4=0

Simple and best practice solution for 15(x+1)-5(10x+9)+2(5x+3)+4=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15(x+1)-5(10x+9)+2(5x+3)+4=0 equation:


Simplifying
15(x + 1) + -5(10x + 9) + 2(5x + 3) + 4 = 0

Reorder the terms:
15(1 + x) + -5(10x + 9) + 2(5x + 3) + 4 = 0
(1 * 15 + x * 15) + -5(10x + 9) + 2(5x + 3) + 4 = 0
(15 + 15x) + -5(10x + 9) + 2(5x + 3) + 4 = 0

Reorder the terms:
15 + 15x + -5(9 + 10x) + 2(5x + 3) + 4 = 0
15 + 15x + (9 * -5 + 10x * -5) + 2(5x + 3) + 4 = 0
15 + 15x + (-45 + -50x) + 2(5x + 3) + 4 = 0

Reorder the terms:
15 + 15x + -45 + -50x + 2(3 + 5x) + 4 = 0
15 + 15x + -45 + -50x + (3 * 2 + 5x * 2) + 4 = 0
15 + 15x + -45 + -50x + (6 + 10x) + 4 = 0

Reorder the terms:
15 + -45 + 6 + 4 + 15x + -50x + 10x = 0

Combine like terms: 15 + -45 = -30
-30 + 6 + 4 + 15x + -50x + 10x = 0

Combine like terms: -30 + 6 = -24
-24 + 4 + 15x + -50x + 10x = 0

Combine like terms: -24 + 4 = -20
-20 + 15x + -50x + 10x = 0

Combine like terms: 15x + -50x = -35x
-20 + -35x + 10x = 0

Combine like terms: -35x + 10x = -25x
-20 + -25x = 0

Solving
-20 + -25x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + -25x = 0 + 20

Combine like terms: -20 + 20 = 0
0 + -25x = 0 + 20
-25x = 0 + 20

Combine like terms: 0 + 20 = 20
-25x = 20

Divide each side by '-25'.
x = -0.8

Simplifying
x = -0.8

See similar equations:

| 7z-9=3 | | 4/3=10/x | | -4p=44 | | 11-a=13 | | 2x+14=-28 | | 6(-6x+4)=-8(4x-6) | | -x-13+25=-3+52 | | 75x-2=-14 | | (12x+1)=(20x+19) | | 5(r-8)-4(6r-4)=-8r-8r | | 2x=5x+21-6 | | 3(1+11)= | | 5a^2+60a+180=0 | | 3x^2-18x-19=0 | | 2(1+x)=3(x+4) | | 9x+70=360 | | 2x(x-4)(x+8)=0 | | 3(5p-3)=5(p-1) | | 14x-3(2x-5)+2(5x-3)=6-5(2x-9) | | 3(y+30)=6y-4 | | 5(v-5)+3(v+2)=-4v+7+3v-2 | | 3(x+5)=5x+2.5 | | 117=6x-12+3x+3 | | (34-2)y=8 | | 8(5x-3)+4(1-8x)=3x-8+3x-2 | | 4u^2-2u=0 | | 10x5/2 | | 2p-10)/(8p-40) | | 6(9d)=3d | | 180=x+(0.05+x) | | (9x-2y)-(6x+2y)= | | 6(x-4)-4=8 |

Equations solver categories